Resin-based composite material and preparation method thereof

By introducing furyl bisphenol monomer, epoxy resin and nanoreinforced filler into the resin-based composite material, and adjusting the weight ratio of the resin matrix to the reinforced fiber, the problem of insufficient toughness of the composite material is solved, significantly improving its toughness and mechanical strength, and improving overall performance.

CN119684745APending Publication Date: 2025-03-25ZHONGFU SHENYING (SHANGHAI) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856783.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The resin-based composites have poor toughness in the direction perpendicular to the reinforcing fibers, limiting their application range.

Method used

By introducing the combination of furylbisphenol monomer and epoxy resin into the resin matrix, as well as nanoreinforced fillers, the weight ratio of the resin matrix to the reinforced fiber is adjusted, and a specific hot melting and curing process is adopted to improve the toughness and mechanical strength of the composite material.

Benefits of technology

It significantly improves the toughness and mechanical strength of composite materials, improves its comprehensive performance, and makes it more widely used in the aerospace, automobile industry and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684745A_ABST
    Figure CN119684745A_ABST
Patent Text Reader

Abstract

The invention discloses a resin-based composite material and a preparation method thereof, and relates to the technical field of composite materials. The resin-based composite material comprises a resin matrix and reinforced fibers, wherein the resin matrix comprises the following components in parts by weight: 182.5-218.5 parts of epoxy resin; 5.0 to 12.5 parts by weight of a furyl bisphenol monomer; 5.8 to 8.6 parts by weight of a nano reinforced filler; 3.5-8.2 parts by weight of a curing agent; the weight ratio of the resin matrix to the reinforced fibers is (2.62-4.96): 1. The resin-based composite material disclosed by the invention has excellent comprehensive properties such as toughness and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a resin-based composite material and a preparation method thereof. Background Art

[0002] Resin-based composite materials are a type of composite materials that are made of resin as a matrix material and a reinforcing material. Among them, the reinforcing material usually includes reinforcing fibers such as carbon fiber, glass fiber, and aramid fiber. Resin-based composite materials are widely used in aerospace, automotive industry, wind energy and other fields due to their advantages such as light weight and high strength. However, due to the significant anisotropy of the reinforcing fibers, the toughness of the composite material in the direction perpendicular to the reinforcing fibers is poor, which limits the application of fiber-reinforced resin-based composite materials. Summary of the invention

[0003] In order to solve the above technical problems, the present application aims to provide a resin-based composite material and a preparation method thereof, wherein the resin-based composite material has the advantage of high toughness.

[0004] According to a first aspect of the present application, a resin-based composite material is provided, the resin-based composite material comprising a resin matrix and reinforcing fibers, the resin matrix comprising the following components in parts by weight:

[0005]

[0006] The weight ratio of the resin matrix to the reinforcing fibers is 2.62-4.96:1.

[0007] In some embodiments of the present application, the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 1:10.50-12.23.

[0008] In some embodiments of the present application, the reinforcing fiber is 50.0-75.0 parts by weight.

[0009] In some embodiments of the present application, the nano-reinforced filler includes a combination of one or more of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-montmorillonite;

[0010] The curing agent includes an amine curing agent.

[0011] In some embodiments of the present application, the resin-based composite material further includes 4.0-7.5 parts by weight of an ultraviolet light absorber.

[0012] In some embodiments of the present application, the ultraviolet light absorber includes a combination of one or more of a benzotriazole ultraviolet light absorber, a benzophenone ultraviolet light absorber, and a triazine ultraviolet light absorber.

[0013] According to a second aspect of the present application, a method for preparing a resin-based composite material is provided. The method for preparing a resin-based composite material is used to prepare the resin-based composite material as described above. The method comprises:

[0014] The resin matrix is ​​melted under a first preset condition and cooled to form a film to form a resin adhesive film;

[0015] Laying the resin film on the reinforcing fibers and impregnating under a second preset condition to obtain a prepreg;

[0016] The prepreg is cured under a third preset condition to obtain the resin-based composite material.

[0017] In some embodiments of the present application, the first preset condition includes: the hot melt temperature is 80-85°C, the cooling film forming temperature is 10-15°C;

[0018] The second preset condition includes: the temperature is 80-90°C;

[0019] The third preset condition includes:

[0020] In the first stage, the temperature is raised to 135-145°C at a heating rate of 2-6°C / min, and the pressure is raised to 5-7 Bar at a pressure increase rate of 0.4-0.6 Bar / min, and maintained for 85-95 minutes;

[0021] In the second stage, the temperature is raised to 175-185°C at a heating rate of 2-6°C / min and maintained for 170-190min;

[0022] In the third stage, the temperature is lowered to 55-65°C at a cooling rate of 1-2°C / min and then the pressure is released.

[0023] In some embodiments of the present application, before hot-melting the resin matrix under the first preset condition to form a resin adhesive film, the preparation method further includes:

[0024] Mixing the epoxy resin and the furanyl bisphenol monomer under a fourth preset condition to obtain a first mixture;

[0025] mixing the first mixture with the nano-enhanced filler under fifth preset conditions to obtain a second mixture;

[0026] The second mixture is mixed with the curing agent under a sixth preset condition to obtain the resin matrix.

[0027] In some embodiments of the present application, the fourth preset condition includes: temperature of 85-95°C, stirring speed of 200-400r / min, and time of 25-35min;

[0028] The fifth preset condition includes: temperature of 75-85°C, stirring speed of 100-300r / min, and time of 25-35min;

[0029] The sixth preset condition includes:

[0030] In the first stage, the temperature is 85-95°C, the stirring speed is 150-350r / min, and the time is 10-15min;

[0031] In the second stage, the temperature is 145-155°C, the stirring speed is 300-500r / min, and the time is 10-15min.

[0032] The technical solution provided by this application may have the following beneficial effects:

[0033] The present application can significantly improve the toughness of the composite material by combining furanyl bisphenol monomer with epoxy resin, and can significantly improve the mechanical strength of the composite material by introducing nano-reinforced fillers, thereby improving the comprehensive performance of the composite material.

[0034] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0036] Figure 1 The present invention is a flow chart of a method for preparing a resin-based composite material according to an exemplary embodiment. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in combination with the embodiments of the present application and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0038] The present application provides a resin-based composite material, which includes a resin matrix and reinforcing fibers, wherein the resin matrix includes the following components in parts by weight: 182.5-218.5 parts by weight of epoxy resin; 5.0-12.5 parts by weight of furanyl bisphenol monomer; 5.8-8.6 parts by weight of nano-reinforced filler; 3.5-8.2 parts by weight of curing agent; and the weight ratio of the resin matrix to the reinforcing fibers is 2.62-4.96: 1. The present application can significantly improve the toughness of the composite material by combining the furanyl bisphenol monomer with the epoxy resin, and can significantly improve the mechanical strength of the composite material by introducing the nano-reinforced filler, thereby improving the comprehensive performance of the composite material.

[0039] Some specific implementation modes described below are intended to facilitate those skilled in the art to understand the present embodiment, and the present embodiment is not limited to some specific implementation modes described below.

[0040] In an exemplary embodiment, the present application provides a resin-based composite material, the resin-based composite material comprising a resin matrix and reinforcing fibers, the resin matrix comprising the following components in parts by weight:

[0041]

[0042] The weight ratio of resin matrix to reinforcing fiber is 2.62-4.96:1.

[0043] Furanyl bisphenol monomer is a bisphenol compound containing a furan ring structure, which has excellent thermal stability and mechanical properties. In this embodiment, the toughness of the composite material can be significantly improved by combining the furanyl bisphenol monomer with the epoxy resin; nano-reinforced filler refers to toughening particles with a particle size of nanometers. In this embodiment, the introduction of nano-reinforced filler can significantly improve the mechanical strength of the composite material, thereby improving the comprehensive performance of the composite material.

[0044] The epoxy resin includes one or more combinations of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and novolac epoxy resin. For example, the epoxy resin includes bisphenol A epoxy resin and bisphenol S epoxy resin in a weight ratio of 2.5-3.2:1. The reinforcing fiber includes one or more combinations of carbon fiber, glass fiber, aramid fiber, and basalt fiber.

[0045] Exemplarily, in one embodiment, the resin-based composite material includes a resin matrix and reinforcing fibers, and the resin matrix includes the following components in parts by weight:

[0046]

[0047] The weight ratio of resin matrix to reinforcing fiber is 2.62:1.

[0048] In another embodiment, the resin-based composite material includes a resin matrix and reinforcing fibers, wherein the resin matrix includes the following components in parts by weight:

[0049]

[0050] The weight ratio of resin matrix to reinforcing fiber is 3.25:1.

[0051] In another embodiment, the resin-based composite material includes a resin matrix and reinforcing fibers, wherein the resin matrix includes the following components in parts by weight:

[0052]

[0053] The weight ratio of resin matrix to reinforcing fiber is 4.96:1.

[0054] In an exemplary embodiment, the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 1:10.50-12.23.

[0055] In this embodiment, by controlling the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin, the composite material can maintain good comprehensive properties such as toughness and mechanical properties. Exemplarily, the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 1:10.50, 1:10.98, 1:11.32, 1:11.88, 1:12.23. The weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin can also be any ratio between the exemplary weight ratios, for example, the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin can also be any ratio between 1:10.98-1:11.32.

[0056] In an exemplary embodiment, the reinforcing fiber is 50.0-75.0 parts by weight.

[0057] In this embodiment, the amount of the reinforcing fiber can be 50.0 parts by weight, 54.6 parts by weight, 63.7 parts by weight, 69.0 parts by weight, and 75.0 parts by weight. The amount of the reinforcing fiber can also be any part by weight between the exemplary amounts, for example, the amount of the reinforcing fiber can also be any part by weight between 54.6-69.0.

[0058] In an exemplary embodiment, the nano-reinforced filler includes a combination of one or more of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-montmorillonite.

[0059] Nano-reinforced fillers can be nano-silicon dioxide, nano-aluminum oxide, and nano-titanium dioxide. The above nano-oxides can not only play a toughening role on the composite material, but also improve the thermal stability of the epoxy resin-based composite material and reduce the heat of the combustion process; nano-reinforced fillers can also be nano-montmorillonite. Nano-montmorillonite, as a silicate mineral material, can not only improve the impact strength and dimensional stability of the epoxy resin-based composite material, but also improve the thermal stability and flame retardant properties of the composite material. In the present embodiment, the nano-reinforced filler can be one of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-montmorillonite, or can be nano-silicon dioxide and nano-montmorillonite with a weight ratio of 3.6-4.7:1. Through the synergistic cooperation of nano-silicon dioxide and nano-montmorillonite, while effectively improving the mechanical properties such as tensile strength, flexural strength, and modulus of the epoxy resin-based composite material, the thermal stability of the composite material can be improved to improve the flame retardant properties of the composite yield rate and effectively improve the dripping problem of the composite material combustion process. The particle size of the nano-reinforced filler may be 10-500 nm, for example, the particle size D50 of nano-silicon dioxide is 20-30 nm, and the particle size of nano-montmorillonite is 200-250 nm.

[0060] In an exemplary embodiment, the curing agent includes an amine curing agent.

[0061] In this embodiment, an amine curing agent can react chemically with the epoxy group in the epoxy resin to form a three-dimensional network structure. The amine curing agent can be, for example, a combination of one or more of diethylenetriamine, triethylenetetramine, 1,3-diamino-2,2,4-trimethylcyclohexane, N-(3-aminopropyl)dimethylamine, and dipropylenetriamine. For example, the amine curing agent includes diethylenetriamine and 1,3-diamino-2,2,4-trimethylcyclohexane in a weight ratio of 1.5-2.0:1.

[0062] In an exemplary embodiment, the resin-based composite material further includes 4.0-7.5 parts by weight of an ultraviolet light absorber.

[0063] In this embodiment, the addition of the ultraviolet light absorber can improve the weather resistance of the composite material and avoid the material aging problem caused by ultraviolet light radiation of the composite material.

[0064] In an exemplary embodiment, the ultraviolet light absorber includes a combination of one or more of a benzotriazole ultraviolet light absorber, a benzophenone ultraviolet light absorber, and a triazine ultraviolet light absorber.

[0065] Benzotriazole ultraviolet light absorbers can strongly absorb ultraviolet light with a wavelength of 310-385nm and have good stability; benzotriazole ultraviolet light absorbers can be one or more of UV-P, UV-326, and UV-327, for example. Benzophenone ultraviolet light absorbers can absorb ultraviolet light with a wavelength of 280-380nm, have good stability and low volatility, and benzophenone ultraviolet light absorbers can be UV-531, for example. Triazine ultraviolet light absorbers can absorb ultraviolet light with a wavelength of 280-380nm, have high efficiency and stability, and triazine ultraviolet light absorbers can be one or more of UV-1164, UV-400, and UV-425, for example. In this embodiment, the ultraviolet light absorber can be one of a benzotriazole ultraviolet light absorber, a benzophenone ultraviolet light absorber, and a triazine ultraviolet light absorber, or it can be a plurality of the above ultraviolet light absorbers. For example, the ultraviolet light absorber can be a benzotriazole ultraviolet light absorber or a triazine ultraviolet light absorber in a weight ratio of 1:0.4-0.6.

[0066] like Figure 1 As shown, an exemplary embodiment of the present application provides a method for preparing a resin-based composite material. The method for preparing a resin-based composite material is used to prepare the above resin-based composite material. The preparation method includes:

[0067] S110, melting the resin matrix under a first preset condition and cooling the resin matrix to form a resin adhesive film.

[0068] In step S110, a hot melt coating process can be used to form a resin film. The first preset condition includes: a hot melt temperature of 80-85°C and a cooling film forming temperature of 10-15°C. For example, the temperature of the coating roller is controlled at 80°C, and the temperature of the melt plate is controlled at 85°C to melt the resin matrix; the temperature of the cooling roller is controlled at 12°C. When hot melt coating is performed, the thickness of the resin film is controlled by the gap between the metering roller and the coating roller, wherein the gap between the metering roller and the coating roller is set to 0.02-0.04mm.

[0069] S120, laying a resin film on the reinforcing fibers, and impregnating the resin film under a second preset condition to obtain a prepreg.

[0070] In step S120, the reinforcing fiber can be carbon fiber. Before use, the carbon fiber needs to be subjected to a yarn spreading treatment, which can improve the mechanical properties of the composite material and improve the surface smoothness of the composite material. Among them, the second preset condition includes: the temperature is 80-90°C. The resin film is spread on the reinforcing fiber, and the hot melt dipping method is used for dipping to obtain a prepreg; wherein, a dipping roller is used during dipping to achieve uniform dipping; the dipping roller is provided with three heating zones and one cooling zone, and the temperatures of the heating zones are respectively set at 80°C, 85°C, and 90°C, the temperature of the cooling zone is 20°C, and the gap between the pressing rollers is 0.35-0.40mm.

[0071] S130, curing the prepreg under a third preset condition to obtain a resin-based composite material.

[0072] In step S130, the prepreg can be heated and cured by a multi-stage heating method, which can improve the curing efficiency and curing speed. Among them, the third preset condition includes:

[0073] In the first stage, the temperature is raised to 135-145°C at a heating rate of 2-6°C / min, and the pressure is raised to 5-7 Bar at a pressure increase rate of 0.4-0.6 Bar / min, and maintained for 85-95 minutes;

[0074] In the second stage, the temperature is raised to 175-185°C at a heating rate of 2-6°C / min and maintained for 170-190min;

[0075] In the third stage, the temperature is lowered to 55-65°C at a cooling rate of 1-2°C / min and then the pressure is released.

[0076] Exemplarily, in one embodiment, the third preset condition includes:

[0077] In the first stage, the temperature was raised to 135°C at a heating rate of 2°C / min, and the pressure was raised to 5 Bar at a pressure rate of 0.4 Bar / min, and maintained for 85 min.

[0078] In the second stage, the temperature was raised to 175°C at a heating rate of 2°C / min and maintained for 170 min;

[0079] In the third stage, the temperature was lowered to 55°C at a cooling rate of 1°C / min and then the pressure was released.

[0080] In another embodiment, the third preset condition includes:

[0081] In the first stage, the temperature was raised to 140°C at a heating rate of 4°C / min, and the pressure was raised to 6 Bar at a pressure rate of 0.5 Bar / min, and maintained for 90 min.

[0082] In the second stage, the temperature was raised to 180°C at a heating rate of 4°C / min and maintained for 180 min;

[0083] In the third stage, the temperature was lowered to 60°C at a cooling rate of 1.5°C / min and then the pressure was released.

[0084] In another embodiment, the third preset condition includes:

[0085] In the first stage, the temperature was raised to 145°C at a heating rate of 6°C / min, and the pressure was raised to 7 Bar at a pressure rate of 0.6 Bar / min, and maintained for 95 min.

[0086] In the second stage, the temperature was raised to 185 °C at a heating rate of 6 °C / min and maintained for 190 min;

[0087] In the third stage, the temperature was lowered to 65°C at a cooling rate of 2°C / min and then the pressure was released.

[0088] In an exemplary embodiment, before the resin matrix is ​​hot-melted under a first preset condition to form a resin adhesive film, the preparation method further comprises:

[0089] S210, mixing the epoxy resin and the furanyl bisphenol monomer under a fourth preset condition to obtain a first mixture.

[0090] In step S210, the fourth preset conditions include: temperature of 85-95°C, stirring speed of 200-400 r / min, and time of 25-35 min.

[0091] Exemplarily, in one embodiment, the fourth preset condition includes: temperature of 85° C., stirring speed of 200 r / min, and time of 35 min.

[0092] In another embodiment, the fourth preset condition includes: temperature of 90° C., stirring speed of 300 r / min, and time of 30 min.

[0093] In another embodiment, the fourth preset condition includes: temperature of 95° C., stirring speed of 400 r / min, and time of 25 min.

[0094] S220, mixing the first mixture with the nano-reinforced filler under fifth preset conditions to obtain a second mixture.

[0095] In step S220, the fifth preset condition includes: temperature of 75-85°C, stirring speed of 100-300 r / min, and time of 25-35 min.

[0096] Exemplarily, in one embodiment, the fifth preset condition includes: temperature of 75° C., stirring speed of 100 r / min, and time of 35 min.

[0097] In another embodiment, the fifth preset condition includes: temperature of 80° C., stirring speed of 200 r / min, and time of 30 min.

[0098] In another embodiment, the fifth preset condition includes: temperature of 85° C., stirring speed of 300 r / min, and time of 25 min.

[0099] S230, mixing the second mixture with the curing agent under a sixth preset condition to obtain a resin matrix.

[0100] In step S230, the sixth preset condition includes:

[0101] In the first stage, the temperature is 85-95°C, the stirring speed is 150-350r / min, and the time is 10-15min;

[0102] In the second stage, the temperature is 145-155°C, the stirring speed is 300-500r / min, and the time is 10-15min.

[0103] Exemplarily, in one embodiment, the sixth preset condition includes:

[0104] In the first stage, the temperature was 85°C, the stirring speed was 150 r / min, and the time was 15 min;

[0105] In the second stage, the temperature was 145°C, the stirring speed was 300 r / min, and the time was 15 min.

[0106] In another embodiment, the sixth preset condition includes:

[0107] In the first stage, the temperature was 90°C, the stirring speed was 250 r / min, and the time was 12 min;

[0108] In the second stage, the temperature was 150°C, the stirring speed was 400 r / min, and the time was 12 min.

[0109] In another embodiment, the sixth preset condition includes:

[0110] In the first stage, the temperature was 95°C, the stirring speed was 350 r / min, and the time was 10 min;

[0111] In the second stage, the temperature was 155°C, the stirring speed was 500 r / min, and the time was 10 min.

[0112] The specific implementation methods of the present application are further described below in conjunction with preferred embodiments, and examples of preferred value ranges of each component in the resin-based composite material provided in the present application are explained in detail.

[0113] Preferred Example 1

[0114] The resin-based composite material comprises a resin matrix and reinforcing fibers, wherein the resin matrix comprises the following components in parts by weight:

[0115]

[0116] The weight ratio of resin matrix to reinforcing fiber is 2.62-4.96:1;

[0117] The weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 10.50-12.23:1.

[0118] Preferred Example 2

[0119] The resin-based composite material comprises a resin matrix and reinforcing fibers, wherein the resin matrix comprises the following components in parts by weight:

[0120]

[0121] The weight ratio of resin matrix to reinforcing fiber is 2.62-4.96:1;

[0122] The weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 10.50-12.23:1;

[0123] The reinforcing fiber is 50.0-75.0 parts by weight.

[0124] Preferred Example 3

[0125] The resin-based composite material comprises a resin matrix and reinforcing fibers, wherein the resin matrix comprises the following components in parts by weight:

[0126]

[0127] The weight ratio of resin matrix to reinforcing fiber is 2.62-4.96:1;

[0128] The weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 10.50-12.23:1;

[0129] The reinforcing fiber is 50.0-75.0 parts by weight;

[0130] The nano-reinforced filler includes one or more combinations of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-montmorillonite;

[0131] The curing agent includes an amine curing agent;

[0132] The ultraviolet light absorber includes a combination of one or more of a benzotriazole ultraviolet light absorber, a benzophenone ultraviolet light absorber, and a triazine ultraviolet light absorber.

[0133] Preferred Example 4

[0134] The resin-based composite material comprises a resin matrix and reinforcing fibers, wherein the resin matrix comprises the following components in parts by weight:

[0135]

[0136] The weight ratio of resin matrix to reinforcing fiber is 4.05-4.54:1;

[0137] The weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 10.50-12.23:1;

[0138] The reinforcing fiber is 50.0-60.0 parts by weight;

[0139] The nano-reinforced filler includes one or more combinations of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-montmorillonite;

[0140] The curing agent includes an amine curing agent;

[0141] The ultraviolet light absorber includes a combination of one or more of a benzotriazole ultraviolet light absorber, a benzophenone ultraviolet light absorber, and a triazine ultraviolet light absorber.

[0142] In order to more clearly explain the technical solution of the present application, the present application lists specific examples of the method for preparing the resin-based composite material, and the beneficial effects of selecting the above-mentioned range of the content of each component will be explained by giving specific experimental data through specific examples.

[0143] Example

[0144] It should be noted that, unless otherwise specified, the raw materials in the following examples can be obtained from the market. Among them, the nano-reinforced filler is nano-silicon dioxide and nano-montmorillonite, the ultraviolet light absorber is benzotriazole, and the curing agent is diethylenetriamine.

[0145] Embodiment 1: A method for preparing a resin-based composite material, comprising the following steps:

[0146] (1) 200 parts by weight of epoxy resin and 10 parts by weight of furanyl bisphenol monomer are mixed and stirred for 30 minutes at a temperature of 90°C and a stirring speed of 300 r / min to obtain a first mixture. The first mixture is mixed and stirred for 30 minutes with 7 parts by weight of nano-silicon dioxide at a temperature of 80°C and a stirring speed of 200 r / min to obtain a second mixture. The third mixture, 5 parts by weight of benzotriazole and 5 parts by weight of diethylenetriamine are mixed and stirred for 12 minutes at a temperature of 90°C and a stirring speed of 250 r / min; then the temperature is raised to 150°C and mixed and stirred at a speed of 400 r / min for 12 minutes to obtain a resin matrix.

[0147] (2) The temperature of the coating roller is set to 80°C, the temperature of the melt plate is set to 85°C, and the temperature of the cooling roller is set to 12°C, and the resin matrix is ​​hot-melted and cooled to form a film to form a resin film.

[0148] (3) After unwinding 50 parts by weight of carbon fiber tow, a resin film is spread on the unwinding carbon fiber tow, and the temperature of the heating zone of the dipping roller is set at 80°C, 85°C, and 90°C, and the temperature of the cooling zone is set at 20°C, so that the resin film is impregnated into the carbon fiber tow to obtain a prepreg.

[0149] (4) The prepreg is spread on the mold and placed in a vacuum tank, the initial vacuum pressure of the vacuum tank is set to ≤0.90 Bar, the temperature is increased to 140°C at a heating rate of 5°C / min, and the pressure is increased to 6 Bar at a pressure of 0.5 Bar / min, and the temperature is maintained at 140°C and the pressure is maintained at 6 Bar for 90 minutes; then the temperature is increased to 180°C at a heating rate of 5°C / min and maintained for 180 minutes; finally, the temperature is reduced to 60°C at a cooling rate of 1.5°C / min, and the pressure is released and the tank is taken out to obtain a composite material.

[0150] In order to more clearly explain the technical solution of the present application, the present application also lists Examples 2-14 of the resin-based composite material, wherein the formulas of Examples 2-14 are shown in Table 1.

[0151] Table 1 shows a specific embodiment of the resin-based composite material in the present application. It should be noted that, except for the parameters listed in Table 1, other parameters of Examples 2-14 are substantially the same as those of Example 1.

[0152] Among them, the ratio C1 in Table 1 is the weight ratio of the resin matrix to the carbon fiber;

[0153] The ratio C2 is the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin;

[0154] The ratio C3 is the weight ratio of nano-silicon dioxide to nano-montmorillonite.

[0155] Table 1 Formulation of the resin-based composite material of the embodiment

[0156] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Epoxy resin 200.0 200.0 200.0 205.3 218.5 200.0 195.0 Furanyl bisphenol monomer 10.0 10.0 10.0 12.5 6.0 8.0 5.0 Nano Silica 7.0 7.0 7.0 7.2 7.8 7.0 6.0 Nano-montmorillonite 0 0 0 0 0 0 0 Benzotriazole 5.0 5.0 5.0 7.5 4.0 5.0 4.5 Diethylenetriamine 5.0 5.0 5.0 6.0 5.5 5.0 6.0 Carbon Fiber 50.0 60.0 65.0 70.0 75.0 50.0 50.0 Ratio C1 4.54:1 3.78:1 3.49:1 3.41:1 3.22:1 4.50:1 4.33:1 Ratio C2 1:11.76 1:11.76 1:11.76 1:10.53 1:15.83 1:13.33 1:17.73 Ratio C3 / / / / / / /

[0157] Table 1 (Continued) Formula of the resin-based composite material of the embodiment

[0158] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Example 13 Embodiment 14 Epoxy resin 195.8 182.5 215.5 210.0 195.7 205.4 200.0 Furanyl bisphenol monomer 9.5 5.0 11.5 11.5 9.5 10.4 11.0 Nano Silica 6.0 5.8 8.6 8.5 5.1 6.1 6.6 Nano-montmorillonite 0 0 0 0 1.4 1.5 1.4 Benzotriazole 5.9 0 4.0 6.5 4.8 5.6 6.0 Diethylenetriamine 4.7 3.5 8.2 6.5 4.5 5.2 6.0 Carbon Fiber 65.0 75.0 50.0 60.0 50.0 55.0 52.0 Ratio C1 3.41:1 2.62:1 4.96:1 4.05:1 4.42 4.26:1 4.44:1 Ratio C2 1:12.63 1:16.9 1:10.21 1:10.50 1:12.23 1:11.41 1:10.53 Ratio C3 / / / / 3.6:1 4.1:1 4.7:1

[0159] Performance Testing

[0160] The properties of the composite materials in Examples 1-14 were tested respectively, and the test results are recorded in Table 2.

[0161] Among them, the flame retardant performance can be measured by the Limiting Oxygen Index (LOI). Generally speaking, LOI < 22% is considered to be a flammable material, 22% ≤ LOI < 27% is considered to be a combustible material, 27% ≤ LOI < 34% is considered to be a flame-retardant material, and LOI > 34% is considered to be a non-combustible material.

[0162] Melt drop performance refers to the ability of a material to resist the formation and dripping of molten droplets when heated or burned, and can be used to evaluate the fire resistance of the material.

[0163] Table 2 Performance test table of the composite material of the embodiment

[0164] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Tensile strength(MPa) 4500 4475 4463 4451 4445 4438 4420 Tensile modulus (MPa) 250 247 243 241 238 235 221 Bending strength(GPa) 2500 2470 2411 2356 2341 2311 2270 Flexural modulus(GPa) 240 238 234 222 215 209 189 Electrical conductivity (S / cm) 9600 9530 9542 9438 9321 9218 9118 Flame retardant properties LOI (%) 40 39 36 33 31 29 23 Whether to drip no no no no no no no

[0165] Table 2 (Continued) Performance test table of the composite material of the embodiment

[0166] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Example 13 Embodiment 14 Tensile strength(MPa) 4410 4397 4450 4486 4513 4520 4526 Tensile modulus (MPa) 222 220 240 249 252 254 255 Bending strength(GPa) 2256 2240 2255 2488 2495 2502 2522 Flexural modulus(GPa) 183 185 220 241 240 243 245 Electrical conductivity (S / cm) 9115 9110 9430 9552 9580 9575 9601 Flame retardant properties LOI (%) 25 23 35 40 40 40 40 Whether to drip no no no no no no no

[0167] It can be seen from the data in Tables 1 and 2 that the resin-based composite material prepared by the method of the present application has excellent mechanical strength, toughness, electrical conductivity and flame retardancy, wherein the furanyl bisphenol monomer, nano-silica and epoxy resin have good compatibility, so that they have a synergistic effect in the epoxy resin system, which can further enhance the mechanical strength, toughness, electrical conductivity and flame retardancy of the carbon fiber composite material. Among them, the composite materials in Example 1 and Examples 11-14 have better comprehensive properties, indicating that the comprehensive properties of the composite materials can be further improved by adjusting the dosage of each component of the resin matrix in the composite material to: 195.7-210.0 parts by weight of epoxy resin, 9.5-11.5 parts by weight of furanyl bisphenol monomer, 6.5-8.5 parts by weight of nano-reinforced filler, 4.8-6.5 parts by weight of ultraviolet light absorber, 4.5-6.5 parts by weight of curing agent, 50.0-60.0 parts by weight of reinforcing fiber, and the weight ratio of the resin matrix to the reinforcing fiber is 4.05-4.54:1, and the weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 1:10.50-12.23.

[0168] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0169] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A resin-based composite material, characterized in that: The resin-based composite material comprises a resin matrix and reinforcing fibers, wherein the resin matrix comprises the following components in parts by weight: The weight ratio of the resin matrix to the reinforcing fibers is 2.62-4.96:

1.

2. The resin-based composite material according to claim 1, characterized in that: The weight ratio of the sum of the furanyl bisphenol monomer and the nano-reinforced filler to the epoxy resin is 1:10.50-12.

23.

3. The resin-based composite material according to claim 1, characterized in that: The reinforcing fiber is 50.0-75.0 parts by weight.

4. The resin-based composite material according to claim 1, characterized in that: The nano-reinforced filler includes one or more combinations of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-montmorillonite; The curing agent includes an amine curing agent.

5. The resin-based composite material according to claim 1, characterized in that: The resin-based composite material further comprises 4.0-7.5 parts by weight of an ultraviolet light absorber.

6. The resin-based composite material according to claim 5, characterized in that: The ultraviolet light absorber includes a combination of one or more of a benzotriazole ultraviolet light absorber, a benzophenone ultraviolet light absorber, and a triazine ultraviolet light absorber.

7. A method for preparing a resin-based composite material, characterized in that: The method for preparing the resin-based composite material is used to prepare the resin-based composite material according to any one of claims 1 to 6, and the method comprises: The resin matrix is ​​melted under a first preset condition and cooled to form a film to form a resin adhesive film; Laying the resin film on the reinforcing fibers and impregnating under a second preset condition to obtain a prepreg; The prepreg is cured under a third preset condition to obtain the resin-based composite material.

8. The method for preparing the resin-based composite material according to claim 7, characterized in that: The first preset conditions include: hot melt temperature of 80-85°C, cooling film forming temperature of 10-15°C; The second preset condition includes: the temperature is 80-90°C; The third preset condition includes: In the first stage, the temperature is raised to 135-145°C at a heating rate of 2-6°C / min, and the pressure is raised to 5-7 Bar at a pressure increase rate of 0.4-0.6 Bar / min, and maintained for 85-95 minutes; In the second stage, the temperature is raised to 175-185°C at a heating rate of 2-6°C / min and maintained for 170-190min; In the third stage, the temperature is lowered to 55-65°C at a cooling rate of 1-2°C / min and then the pressure is released.

9. The method for preparing the resin-based composite material according to claim 7, characterized in that: Before hot-melting the resin matrix under the first preset condition to form a resin adhesive film, the preparation method further comprises: Mixing the epoxy resin and the furanyl bisphenol monomer under a fourth preset condition to obtain a first mixture; mixing the first mixture with the nano-enhanced filler under fifth preset conditions to obtain a second mixture; The second mixture is mixed with the curing agent under a sixth preset condition to obtain the resin matrix.

10. The method for preparing a resin-based composite material according to claim 9, characterized in that: The fourth preset conditions include: temperature of 85-95°C, stirring speed of 200-400r / min, and time of 25-35min; The fifth preset condition includes: temperature of 75-85°C, stirring speed of 100-300r / min, and time of 25-35min; The sixth preset condition includes: In the first stage, the temperature is 85-95°C, the stirring speed is 150-350r / min, and the time is 10-15min; In the second stage, the temperature is 145-155°C, the stirring speed is 300-500r / min, and the time is 10-15min.